The Influence of Credit Risk, Liquidity Risk and Capital Adequacy on Financial Performance in the Conventional Banking Sector Listed on the Indonesian Stock Exchange for the 2021-2023 Period - Rosita, Meyra Alia; Hazmi, Shadrina (CV. Rayyan Dwi Bharata, 2025)
This research aims to examine the influence of credit risk, liquidity risk and capital adequacy on financial performance in the conventional banking sector listed on the Indonesian Stock Exchange for the 2021-2023 period. The sampling technique used in this research is Purposive Sampling. The population in this study was 42 companies and 38 companies met the requirements to be the sample. The type of data used in this research is secondary data and multiple linear regression analysis methods. Credit Risk is measured using Non Performing Loans. Liquidity Risk is measured using the Loan to Deposit Ratio. Capital Adequacy is measured using the Capital Adequacy. The financial performance of banking companies is measured using Return On Assets. The Classical Assumption Test states that the data in this study are normally distributed and produce a regression model that is free from multicollinearity, heteroscedasticity and autocorrelation. Based on the partial test analysis, the results obtained are : (1) Credit Risk has a positive and significant effect on Financial Performance. (2) Liquidity Risk has a positive and significant effect on Financial Performance. (3) Capital Adequacy has no significant effect on Financial Performance. And the results of the F Test in this research show that Credit Risk, Liquidity Risk and Capital Adequacy simultaneously influence Financial Performance. The findings in this research have implications for banking companies to pay careful attention to financial management in order to obtain maximum profits.